Prospective long‐term evaluation of parenteral hydroxocobalamin supplementation in juvenile beagles with selective intestinal cobalamin malabsorption (Imerslund‐Gräsbeck syndrome). (23rd March 2018) - Kook, Peter Hendrik; Reusch, C. E.; Hersberger, M.
Abstract : Background: Prospective studies on maintenance treatment for Beagles with hereditary selective cobalamin (Cbl) malabsorption (Imerslund‐Gräsbeck syndrome, IGS) are lacking. In our experience, measurement of methylmalonic acid (MMA), a Cbl‐dependent metabolite, seems more helpful to monitor Cbl status as compared with serum Cbl concentrations. Objectives: To evaluate a standardized Cbl supplementation scheme in Beagles with IGS. We hypothesized that a single parenteral dose of 1 mg hydroxocobalamin (OH‐Cbl) would maintain clinical and metabolic remission for up to 2 months. Animals: Six client‐owned juvenile Beagles with genetically confirmed IGS and 28 healthy control dogs. Methods: Prospective study. Monthly IM OH‐Cbl (1 mg) supplementation was done over a median of 9 months (range, 6‐13) in 6 dogs, followed by bimonthly (every 2 months) injections in 5 dogs over a median of 6 months (range, 3‐10). Health status was assessed by routine clinical examinations at injection time points and owner observations. Voided urine samples were collected immediately before OH‐Cbl injections for measurement of MMA‐to‐creatinine concentrations using a gas‐liquid chromatography‐tandem mass spectrometry (GC‐MS) method. Results: All dogs were clinically healthy while receiving monthly and bimonthly OH‐Cbl supplementation. Urinary MMA results in healthy dogs ranged from 1.3 to 76.5 mmol/mol creatinine (median, 2.9). Median urinary MMA concentrations did not differ between dogs with IGS receiving monthly (n = 49; 5.3 mmol/mol creatinine; range, 2.3‐50.4) and bimonthly (n = 31; 5.3 mmol/mol creatinine; range, 1.6‐50) injections. Conclusions and Clinical Importance: A maintenance parenteral dose of 1 mg OH‐Cbl monthly or bimonthly appears adequate in Beagles with IGS monitored by metabolic testing.